The effect of perceived travel risk on revisit intention at Chow Kit Road Market (CKRM), Kuala Lumpur among domestic tourists / Nurul Hasanah Abdul Satar and Ahmad Fitri Amir - Abdul Satar, Nurul Hasanah; Amir, Ahmad Fitri (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The field of tourism research has discovered that the presence of risk has a substantial role in influencing the intention of tourists to travel and their criteria for selecting a travel destination. The relationship between perceived travel risk and intention to revisit among tourists has been extensively investigated but lacks within the context of Malaysia’s domestic tourists. Previous research indicates a strong association between perceived travel risk and intention to revisit. This study focuses on local tourists who have visited Chow Kit Road Market (CKRM) in Kuala Lumpur. The Chow Kit area has a negative reputation as a hazardous district. Therefore, this study aims to investigate the impact of perceived travel risk on domestic tourists’ intention to revisit CKRM. A total of 385 valid responses were collected via convenience sampling technique. SPSS version 28 was utilized for data analysis. This study found that financial risk, time risk, and physical risk are significant, while social risk and psychological risk are not significant in terms of revisit intention at CKRM.